Kualitas Buku Teks “Ajar Basa Jawa” Kelas IV SD Berdasarkan Parameter BSNP Dan Uji Fry - Nurhidayati, Nurhidayati; Suwarna, Suwarna; Wulan, Sri Hertanti; Rubiyanto, Yayan (Jayapangus Press, 2025)
The assessment of the quality of textbooks is important to be studied in order to measure their suitability to the needs of students and alignment with the curriculum. The Textbook